Influence of recovery time on warm-up effects in male adolescent athletes - Faigenbaum, A. D.; McFarland, J. E.; Kelly, N. A.; Ratamess, N. A.; Kang, J.; Hoffman, J. R. (Pediatric Exercise Science, 2010)
The purpose of this study was to examine the influence of recovery time following a dynamic warm-up (DY) and a static stretch warm-up (SS) on power performance in adolescent athletes. Following baseline measures, 19 males (16.5 ± 1.1 yrs) performed the vertical jump (VJ) and seated medicine ball toss (MB) at the following time points after DY and SS: 2, 6, 10, 14, 18, 22 min. Analysis of variance revealed that VJ was significantly greater following DY than SS at 2, 6, 10, 14 and 18 min. Main effects indicated a significant increase in VJ from baseline at 2 and 6 min following DY (2.6-3.9%) and a significant decrease in VJ from baseline at 2, 6, 10, 14 and 18 min following SS (-3.2% to -7.0%). No significant interaction effects between DY and SS were observed for MB. These findings indicate that lower body power performance in male adolescent athletes can be enhanced following DY as compared with SS during the first 18 min of the post warm-up period.